Delayed but not Early Treatment with DNase Reduces Organ Damage and Improves Outcome in a Murine Model of Sepsis. Issue 2 (August 2015) - Mai, Safiah H. C.; Khan, Momina; Dwivedi, Dhruva J.; Ross, Catherine A.; Zhou, Ji; Gould, Travis J.; Gross, Peter L.; Weitz, Jeffrey I.; Fox-Robichaud, Alison E.; Liaw, Patricia C.
<x xml:space="preserve">Abstract</x> ABSTRACT Sepsis is characterized by systemic activation of coagulation and inflammation in response to microbial infection. Although cell-free DNA (cfDNA) released from activated neutrophils has antimicrobial properties, it may also exert harmful effects by activating coagulation and inflammation. The authors aimed to determine whether deoxyribonuclease (DNase) administration reduces cfDNA levels, attenuates coagulation and inflammation, suppresses organ damage, and improves outcome in a cecal ligation and puncture (CLP) model of polymicrobial sepsis. Healthy C57Bl/6 mice were subjected to CLP, a surgical procedure involving two punctures of the ligated cecum, or sham surgery (no ligation/puncture). Mice were given DNase or saline by intraperitoneal injection 2, 4, or 6 h after surgery. Two hours after treatment, organs were harvested and plasma levels of cfDNA, interleukin-6 (IL-6), IL-10, thrombin-antithrombin complexes, lung myeloperoxidase, creatinine, alanine transaminase, and bacterial load were quantified. Survival studies were also performed. The CLP-operated mice had rapid time-dependent elevations in cfDNA that correlated with elevations in IL-6, IL-10, and thrombin-antithrombin complexes and had organ damage in the lungs and kidneys. Administration of DNase at 2 h after CLP resulted in increased IL-6 and IL-10 levels and organ damage in the lungs and kidneys. In contrast, DNase administration at 4 or 6 h after CLP resulted in reduced cfDNA and IL-6 levels, increased IL-10, and suppressed organ damage and bacterial dissemination. Deoxyribonuclease administration every 6 h after CLP also rescued mice from death. Our studies are the first to demonstrate that delayed but not early administration of DNase may be protective in experimental sepsis.